Economics and Law - Ivaniuzhenko A. B., Davletshin T. G., Patutina E. S., Guselnikova L. N., Ershova I. G., Kostygova L. A., Vereshchagina L. S., Olkhova L. A. (Economics and Law, 2020)
an attempt to study the cultural problems mediating the behavior of the parties in mandatory pension relations is made. The author draws conclusions about the relationship of the content of oral folk art works and fairy tales by A. Pushkin with the will of Russian citizens as a party of the relations on compulsory pension insurance.
Keywords: фольклор; сказки; folklore; обязательства; общественный договор; пенсионное страхование; антропоморфизм; поэзия А; Пушкина; social contract; pension insurance; commitment; tales; anthropomorphism; Pushkin's poetry